2015
DOI: 10.1007/s11517-015-1364-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution detection of sustained ventricular and supraventricular tachycardia through FPGA-based fuzzy processing of ECG signal

Abstract: The paper presents a field-programmable gate array (FPGA)-based fast processing system with 12-channel high-resolution (24 bits) front-end for ECG signal processing. The implemented high-resolution data conversion makes the system suitable for recording of late potentials of the QRS complex in patients prone to sustained ventricular tachycardia. The system accepts ECG signals through 12 channels and then filtered to minimize baseline wander and power-line interference. The filter outputs are connected to 12 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…With the aim of this solutions, an increasing number of studies have found that relates the parametric importance of different ECG features [40]. According to literature, these parametric factors rely on external or internal variables, which can be referred to as feature dependencies [41,43,45]. Various state-of-the-art classification techniques for different T-wave patterns are sourced from the existing literature [58,59].…”
Section: Methodological Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of this solutions, an increasing number of studies have found that relates the parametric importance of different ECG features [40]. According to literature, these parametric factors rely on external or internal variables, which can be referred to as feature dependencies [41,43,45]. Various state-of-the-art classification techniques for different T-wave patterns are sourced from the existing literature [58,59].…”
Section: Methodological Comparisonmentioning
confidence: 99%
“…In literature, a number of studies found that build a reasonable accuracy level in terms of classification of different T wave episodes, but due to these methods, the difference between flattened T wave and inversion T wave is still unclear [30][31][32][33][34]. Accurate and robust classification of different T wave episodes relies entirely on the identification of the values of T wave parameters especially in terms of T-onset and T-offset [35][36][37][38][39][40][41]. Such findings are further helpful for highlighting the intensity of MI in terms of ST-segment elevation and ST-segment depression [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The suggested diagnostic system based on fuzzy neural is realized on Altera EP1C6Q240C8 FPGA platform to take advantage of FPGA low cost and flexibility to map changes in the proposed algorithm. According to the results obtained by [33], the applied fuzzy neural FPGA based realization was fast with very high detection accuracy comparing to other QRS methods detection.…”
Section: ) Detection and Diagnostic Implementationmentioning
confidence: 95%
“…In [33], present FPGA realization aims to detect QRS complex and utilized it for ventricular and supraventricular tachycardia diagnosis in real-time manner. The research applies the fuzzy entropy measure of high resolution ECG sample values to neural network.…”
Section: ) Detection and Diagnostic Implementationmentioning
confidence: 99%